COMMUNITY DEVELOPMENT BASED ON HUMAN-CENTERED DEVELOPMENT THROUGH PENGABDI MUDA #11 IN RINCA ISLAND: PENGABDIAN MASYARAKAT BERBASIS HUMAN-CENTERED DEVELOPMENT MELALUI PENGABDI MUDA #11 DI PULAU RINCA - Muchlashin, Anif; Robiyanto, Muhammad (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Rinca Island in West Manggarai, NTT, faces challenges in health, education, economy, and tourism, including limited access to health services, low literacy rates, a struggling economy, and untapped tourism potential. These issues have kept the area classified as a 3T region, indicating low welfare levels. To address these challenges, Arah Pemuda Indonesia, along with 40 delegates from various regions, implemented the Pengabdi Muda #11 program over four days to provide community service. Objective: The program aims to enhance community awareness and capacity in health, education, economy, and tourism through a Human-Centered Development approach. Method: The initiative included socialization, counseling, workshops, and hands-on demonstrations, engaging the community directly. Key partners were local government, healthcare professionals, business stakeholders, and academics, with evaluations conducted using pre-tests and post-tests to measure skill development. Results: The program led to significant increases in public health awareness, educational literacy, local economic skills, and understanding of tourism potential. Conclusion: The initiative positively impacted the Rinca Island community by enhancing individual and community capacities. Continued programs are expected to further support sustainable local development.